Bordeaux wines and the potential of export to the Czech Republic - Dupkalová, Dana (2023)
The aim of this bachelor thesis is to analyze the French wine industry with a particular focus on the Bordeaux wines and analyze the potential export of this type of wine to the Czech Republic. The first chapter of the thesis is dedicated to the international wine market. It introduces general information on wine, its production, characteristics, and various types. Consequently, it shifts the focus to the French wine market. There, it delves into France´s performance in terms of production and consumption with a particular detail given to Bordeaux wines and their peculiarity. The second chapter is consecrated to the Czech wine market. It talks about wine consumption in the Czech Republic and analyzes the key factors influencing the demand for wine in the Czech Republic. Two research methods are used to reach the aim of the thesis – qualitative analysis and quantitative analysis.